Dampak Perang Batak pada Tahun 1878 - 1907 Terhadap Penyebaran Agama Kristen di Sumatera Utara - Shelyn Fransisca Natalia; Muhammad Fendi Aditya (Tsaqofah, 2019)
This study aims to: (1) Know that the Indonesian nation has been colonized by the Dutch for a period of centuries. (2) Knowing the arrival of the Dutch, they wanted to shock their power in Indonesia. (3) Knowing the causes of the Batak War. (4) Knowing the impact of the Batak war on the spread of Christianity in Batak North Sumatra. Research Methods: This study used a literature study data collection and then found the following facts: Various policies implemented by the Dutch aimed to seek profit from the spices in Indonesia so that they could provide profit for the Dutch, while the people of Indonesia who were ruled suffered severe suffering. Apart from pursuing a policy of seeking maximum profit in their colonies, the Dutch also implemented a political policy of Pax Netherlandica to support missionary activities. The policies made by the Dutch in order to perpetuate their power in Indonesia led to a reaction of resistance by the people against the Dutch policies that tormented the Indonesian people. The spread of colonialism carried out by the Dutch controlled Indonesian territories such as Java, Madura and Sumatra. The resistance was led by local leaders who were mostly worried about the politics of Pax Netherlandica which undermined their power. There was resistance by the Indonesian people and their leaders, one of which was the Tapanuli resistance or Tapanuli war or Batak War which lasted for 20 years led by Sisingamangaraja XII.